Features of the prevalence of chronic cystitis among adolescents - N. Saidakova; L. Startseva; A. Klys; O. Onyskiv; V. Нrodzinkiyy (Ukrainian Journal of Nephrology and Dialysis, 2022)
Abstract. The present study aimed to assess the dynamics of the incidence, and prevalence of chronic cystitis in adolescents of both sexes in a comparative regional aspect in Ukraine.Methods. Data from official statistics for 2013-2017 were used. Incidence and prevalence indicators are presented in a comparative aspect by sex and administrative categories of Ukraine.Results. It was found that with higher rates among girls, the growth rate of morbidity and prevalence among boys is much higher.Conclusions. Territorial features have been identified and those that require the primary attention of specialists to make appropriate decisions.